Anti-inflammatory and hypolipidemic mechanisms of Eucalyptus tereticornis leaf extract (2022)
ABSTRACT: Obesity is a complex condition with adipocyte hypertrophy as an important source for the development of adipose tissue inflammation that plays a central role in the pathogenesis of many obesity-associated complications. Ursolic acid (UA), Oleanolic acid (OA) and Ursolic acid lactone (UAL) are the main molecules (78%) in a Eucalyptus tereticornis (Eu) extract (OBE100). This enriched-triterpene fraction mixed with unknown minor metabolites has a synergistic effect providing superior anti-inflammatory and hypolipidemic effects than reconstituted triterpenoid.